2008
DOI: 10.1002/pc.20545
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of multiple carbon fillers on the rheology of liquid crystal polymer based resins

Abstract: Adding conductive carbon fillers to insulating thermoplastic resin increases composite electrical and thermal conductivity. Often, as much of a single type of carbon filler is added to achieve the desired conductivity, while still allowing the material to be molded into a bipolar plate for a fuel cell. In this study, varying amounts of three different carbons (carbon black, synthetic graphite particles, and carbon fiber) were added to Vectra A950RX liquid crystal polymer. The rheology of resulting single fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In Figures 14 and 15, as CB is added to the PC, the steady shear viscosities of the resulting composites are observed to increase from 700 to 2000 Pa s. This is the expected behavior, as most carbon/thermoplastic composites show an increase in viscosity as filler loading is increased 27, 42–46. At all shear rates, the viscosities rise as CB is added to the polycarbonate.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In Figures 14 and 15, as CB is added to the PC, the steady shear viscosities of the resulting composites are observed to increase from 700 to 2000 Pa s. This is the expected behavior, as most carbon/thermoplastic composites show an increase in viscosity as filler loading is increased 27, 42–46. At all shear rates, the viscosities rise as CB is added to the polycarbonate.…”
Section: Resultsmentioning
confidence: 67%
“…11). This is unusual behavior, as most carbon/thermoplastic composites show an increase in viscosity as filler loading is increased 27, 42–46. At still higher loadings (4–8 wt % CNT in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…9). Figure 9 includes data reported here and previously reported,39 which include combinations of fillers with 4 wt % CB (4CB), 40 wt % SG (40SG), and 10 wt % CF (10CF). Two‐filler blends of SG and CF with Vectra follow the same curve of the relative viscosity versus the volume fraction of carbon as was traced by the single‐component composites of these materials.…”
Section: Resultsmentioning
confidence: 99%
“…The bipolar plates had density of 1.6 gcm -3 , specific bulk conductivities 150 Scm -1 and material prices between 2 and 10 Euro kg -1 . Even though, the investigations showed that the electrical conductivity and ability of injection moulding process can be improved significantly, three carbon fillers always resulted in an increased viscosity [44] . Fig.…”
Section: Electrically Conductive Carbonaceous Fillersmentioning
confidence: 97%